KLASIFIKASI EMOSI PADA LIRIK LAGU DALAM ALBUM MENGUDARA KARYA IDGITAF: KAJIAN PSIKOLOGI SASTRA - Lubis, Maymunah; Hidayatullah, Syarif (Universitas Negeri Makassar, 2024)
This research was conducted to analyze emotion classification in song lyrics in the album Mengudara by Idgitaf. The method applied in this research is a qualitative research method using David Krech's emotion classification theory to analyze songs. The data source used in this research is the text of the song lyrics in the album Mengudara by Idgitaf, which was released on July 28, 2023. The data collection technique in this research uses literature study techniques, namely the observation and note-taking techniques. The data analysis technique used in this research is content analysis. The results of this study indicate that the song lyrics on the album Mengudara by Idgitaf found 10 types of emotions out of 12 types of emotions in accordance with the theory of emotion classification proposed by David Krech. The dominant emotion in the album is fear.